Integrating GPS with GLONASS for high‐rate seismogeodesy - Jianghui Geng; Peng Jiang; Jingnan Liu (Geophysical Research Letters)
Abstract High‐rate GPS is a precious seismogeodetic tool to capture coseismic displacements unambiguously and usually improved by sidereal filtering to mitigate multipath effects dominating the periods of tens of seconds to minutes. We further introduced GLONASS (Globalnaya navigatsionnaya sputnikovaya sistema) data into high‐rate GPS to deliver over 2000 24 h displacements at 99 stations in Europe. We find that the major displacement errors induced by orbits and atmosphere on the low‐frequency band that are not characterized by sidereal repeatabilities can be amplified markedly by up to 40% after GPS sidereal filtering. In contrast, integration with GLONASS can reduce the noise of high‐rate GPS significantly and near uniformly over the entire frequency band, especially for the north components by up to 40%, suggesting that this integration is able to mitigate more errors than only multipath within high‐rate GPS. Integrating GPS with GLONASS outperforms GPS sidereal filtering substantially in ameliorating displacement noise by up to 60% over a wide frequency band (e.g., 2 s–0.5 days) except a minor portion between 100 and 1000 s. High‐rate multi‐GNSS (Global Navigation Satellite System) can be enhanced further by sidereal filtering, which should however be carefully implemented to avoid adverse complications of the noise spectrum of displacements.